DESIGN THINKING AS AN INNOVATIVE TEACHING METHOD FOR MEDIA AND COMMUNICATION COURSES - G., Suresh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The objective of this research is to show how to design, implement, and establish how and why the Design thinking-based innovative teaching method is more effective. Following an action research method, a design thinking-based innovative pedagogy was introduced among the first-year postgraduate media students to teach a few modules of the course 'Television and Video Production'. An ill-defined story idea for an animated sci-fi television series was presented to student groups, and they were asked to develop upon the idea as well as provide some creative solutions to the problems. The entire activity was carried out in five different stages, such as Empathize, Define, Ideate, Prototype, and Test. At the end of the activity, the effectiveness of design thinking as an innovative method was analyzed. The findings suggest that design thinking was effective in imparting 21st-century skills, such as empathy, critical thinking, problem-solving, collaboration, creativity, and innovation.